Amplitude Control of Single Phase Capacitor Motor - N. Barsoum, Fatin (Journal of Engineering and Sustainable Development, 2010)
The method is proposed to study the performance of a single-phase capacitor motor with amplitude control. This is clearly shown by controlling the speed of the motor by varying the applied voltage to the control voltage while the excitation voltage is constant. The obtained results show the validity of the method and the accuracy of the equations derived in this work.